2016
DOI: 10.1063/1.4943607
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of localized current anomalies in polymer electrolyte fuel cells from magnetic flux density measurements

Abstract: In this paper, we propose novel inversion methods to estimate defects or localized current anomalies in membrane electrode assemblies (MEAs) in polymer electrolyte fuel cells (PEFCs). One method is an imaging approach with L1-norm regularization that is suitable for estimation of focal anomalies compared to Tikhonov regularization. The second is a complex analysis based method in which multiple pointwise current anomalies can be identified directly and algebraically from the measured magnetic flux density.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 6 publications
0
18
0
Order By: Relevance
“…In particular, it has been reported that a vertical current flowing perpendicular to the MEA dominantly generates the magnetic flux density. Nara et al reported the validity of 2-D modeling for computing the magnetic flux density outside the fuel cells [6]. In the present paper, we also assume a 2-D current source model: let an MEA be on z = 0, and let the current I flow in the −z direction perpendicular to the MEA.…”
Section: Magnetic Flux Density Produced By a Current Flowing Through mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, it has been reported that a vertical current flowing perpendicular to the MEA dominantly generates the magnetic flux density. Nara et al reported the validity of 2-D modeling for computing the magnetic flux density outside the fuel cells [6]. In the present paper, we also assume a 2-D current source model: let an MEA be on z = 0, and let the current I flow in the −z direction perpendicular to the MEA.…”
Section: Magnetic Flux Density Produced By a Current Flowing Through mentioning
confidence: 99%
“…Although this method is able to model the current density of the fuel cell, it cannot precisely detect the size or shape of defects. Nara et al calculated the external magnetic field from the current density inside the fuel cell using a two-dimensional (2-D) model and proposed a method for predicting the center positions of defects using a complex analysis based-method [6]. However, they were not able to obtain the spatial extent of the defects.…”
Section: Introductionmentioning
confidence: 99%
“…However, these non-destructive methods are difficult to implement in PEMFC stacks. Furthermore, previous studies [30][31][32] used numerous sensors and involved considerable calculation time to realize the same level of accuracy as the PCB method. Hence, installation and control in a PEMFC system are challenging.…”
Section: Introductionmentioning
confidence: 99%
“…The current distribution is derived based on the magnetic flux densities embedded within the fuel cell through Maxwell's equations [29]. Moreover, a three‐dimensional finite element method simulation that converts the environmental magnetic flux around the PEMFC cell was developed to estimate the localized current distribution [30]. However, these non‐destructive methods are difficult to implement in PEMFC stacks.…”
Section: Introductionmentioning
confidence: 99%
“…Yamanshi and al. [33] also investigated fuel cell diagnosis by measuring the magnetic field, and an additional study was done in [34]. In these studies, a genetic algorithm is used to find a linear combination of magnetic field signatures associated to elementary faults.…”
Section: Introductionmentioning
confidence: 99%